Materials Selection. (Education Digest, 1982)
This article presents information about a survey which indicates that challenges to library and curriculum materials in the U.S. are occurring more frequently in recent years, and most institutions do not have effective policies through which to respond to such challenges. The survey was conducted by the Association of American Publishers, the American Library Association, and the Association for Supervision and Curriculum Development. It was titled as "Book and Materials Selection for School Libraries and Classrooms: Procedures, Challenges, and Responses." The report recommends that school districts establish policies for materials selection and for dealing with complaints, and offers general guidelines for such policies.